Effect of Non-Class Fly Ash on Strength Properties of Concrete - Anjeza Alaj; Nexhmi Krasniqi; Tatsuya Numao (Salehan Institute of Higher Education, 2024)
Developing of green construction and reducing CO2emissions in the environment is a priority for industry in the coming years. Recycling fly ash in the concrete industry is a well-known way to reduce environmental impact. Aside from this benefit, there are numerous other positive effects of incorporating fly ash into concrete; however, in this research, the objective is to replace cement with a different percentage of non-class fly ash with high CaO, more than 42%. The analyzed variables are non-class fly ash properties, the effect of fly ash presence on the main properties of concrete and examining the optimum of non-class fly ash in ordinary concrete C-25/30 and high-performance concrete C-50/60. All investigations took place in the laboratory by producing 24 different mix designs and more than 1000 specimens to examine: consistency, setting time, shrinkage, and compressive strength in the short and long terms of curing. Recycling industrial waste in new construction, especially fly ash because of its non-uniform properties, still has some obstacles and is not a practical issue, but the future must be environmentally friendly, and this research proves that the objective of producing sustainable ordinary and high-performance concrete was achieved by replacing 40% of cement with non-class high CaO content fly ash. Doi: 10.28991/CEJ-2024-010-03-02 Full Text: PDF